Corruption Intentions Among Prospective Elites in Ghana: An Economy of Esteem - Tankebe, J.; Karstedt, S.; Adu-Poku, S. (International Criminal Justice Review, 2018)
Besides its multiple harms, corruption undermines the rule of law and impedes the effective functioning of criminal justice institutions. It involves both elites in bending rules and laws as well as police at the bottom of the hierarchy asking for bribes. We analyze corruption intentions within the framework of Brennan and Pettit’s “economy of esteem,” using three main conceptual frameworks: attachment to kinship groups, materialistic orientations, and deterrence. We draw on data from a survey of 530 university students in Ghana to examine predictors of corruption intentions of prospective elites. Our prospective elites were more inclined to resort to influence peddling rather than to pay bribes directly. We find that attitudinal patterns indicative of esteem predict intentions to engage in corrupt exchanges across different agencies and contexts—police, procurement for government, and abuse of power—as well as different types of action, whether bribe payment or nepotism. In contrast, citizenly pride (and self-esteem) motivates integrity across all types of corrupt exchange. Deterrence, in terms of certainty, had a more consistently negative impact on intentions to engage in nepotism than in bribe paying and acceptance, with public procurement being the exception; no effect was found for stigma, and only police nepotism was an exception to the otherwise non-significant effects of severity.
Keywords: Corruption; Economy of esteem; Primordialism; Materialism; Deterrence